Intention Level of Farmers to Use Information Communication Technologies for Agricultural Risk Management in Malaysia - Muhammad Ali; Norsida Man; Farrah Melissa Muharam (Journal of International Agricultural and Extension Education, 2020)
Climate changes are changing intentions of farmers to tackle climate variations in various ways. Information and Communication Technologies are proving to assist farmers to manage agricultural risk timely and with fewer efforts. Intention of farmers to use ICTs in the context of agricultural risk management is important to understand. Therefore, the present study was designed to examine intention of the farmers from the context of Malaysia. The field survey of three selected states was conducted in which 350 farmers were chosen through multi stage cluster sampling technique. The Likert scale items measuring 1 as strongly disagree to 5 as strongly agree were used in the research instrument to assess intention of the respondents. The findings revealed that the farmers showed positive intention to use ICTs for agricultural risk management from the future lens. The overall level of intention was also high. However, internet speed, small screen display and battery issues could halt intention of the farmers to harness potential of digital technologies as reported by the farmers. Thus, the study recommends that agricultural extension service providers are required to introduce various digital skill development programs for the farmers exclusively resource poor and less digital familiar farmers to reduce the risk in the agricultural sector stem from climate changes.
Keywords: intention; farmers; ICTs; agricultural risk management; Malaysia